Guru Agama Katolik sebagai pelayan Gereja di Paroki Santo Yosef Delitua dalam tinjauan Spiritualitas Diakonia - gurusinga, rikha emyya (Pastoralia Jurnal Penelitian Dosen, 2025)
This study aims to explore the role of Catholic Religious Education (CRE) teachers in diaconal engagement at St. Joseph Parish, Delitua. A mixed-method approach was used, combining qualitative and quantitative methods. Qualitative data were obtained through in-depth interviews with CRE teachers, priests, and pastoral leaders, as well as participatory observation during liturgical and social activities. Quantitative data were collected through questionnaires evaluating the frequency and types of CRE teachers’ involvement in church ministry. The results of the study indicate that time constraints, motivation, and lack of community support are the main barriers to implementing diaconal values by teachers. Nevertheless, involvement in diakonia has a positive impact on their teaching quality and spiritual experience. This research provides recommendations to strengthen support and training in order to enhance CRE teachers’ participation in church ministry and the development of diaconal spirituality.